Inclusion Compound Based Approach to Forming Arrays of Artificial Dipolar Molecular Rotors: A Search for Optimal Rotor Structures. (8th October 2012) - Kobr, Lukáš; Zhao, Ke; Shen, Yongqiang; Shoemaker, Richard K.; Rogers, Charles T.; Michl, Josef
<x xml:space="preserve">Abstract</x> Hexagonal tris(o‐phenylenedioxy)cyclotriphosphazene (TPP) is used as ahost for organizing dipolar molecular rotor guests into regular trigonal arrays. Inclusion of molecular rotors with transversely dipolar rotators into TPP channels is followed by solid‐state nuclear magnetic resonance, diifferential scanning calorimetry, X‐ray diffraction, and dielectric spectroscopy. The more polar of the two rotors does not form an inclusion. The second rotor forms two different inclusions differing in crystallite size and the rotational barriers. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>